Comparison of Efficacy of Oral Iron Chelators with Parenteral Chelators in Patients of Β Thalassaemia Major - Shaheen, Masooma (International Journal of Pathology, 2022)
Introduction: Transfusional hemosiderosis is a frequent complication seen in patients with Beta thalassemia major (β thalassemia major). They require regular iron chelation to get rid of excessive iron deposited in different organs of body. It is the need of the hour to find an appropriate iron chelator which can effectively chelate iron and improve the quality of life of these patients.Objective: The aim of this study is to compare efficacy of parenteral iron chelator Desferrioxamine with oral iron chelator Deferasirox in patients of β Thalassemia Major.Materials and Methods: I04 β Thalassemia major patients were randomly divided into 2 groups. Group 1 received parenteral iron chelator and Group 2 received oral iron chelator for one year. Serum ferritin levels were measured at start of study and then 3 monthly for 1 year. Results: Group 1 had 36 (69.2%) males and 16(30.8%) females , Group 2 had 31(59.6%) males and21(40.4%) females. In Group 1 mean Serum Ferritin at 0 month was 3137.75 μg/l (± 1426.06) and at 12 month was 3180.00 μg/l (±1193.61) with difference in Serum Ferritin level from base line of 87.63μg/l (±1370.95). In Group 2 mean Serum Ferritin at 0 month was 2821.77μg/l (±736.51) and at 12 month was 2043.08 μg/l (±863.69) with difference in mean serum ferritin of 759.65 μg/l (±1099.74). Paired t-test was applied to compare means at base line and at 12-month follow-up which showed significant mean predicted improvement from baseline with p value of 0. 008.Conclusion: Oral iron chelators, produce a greater reduction in serum ferritin levels as compared to parenteral iron chelators.